Chapter Il Portogallo nel XVIII secolo - Graziani, Michela (Firenze University Press, 2023)
The first section of the volume aims to describe the Portuguese society of the 18th century through European travel reports, iconographical representations of the city of Lisbon and the cultural ferment through some of the most important Portuguese literary figures of the 18th century.